Analisis Biaya Konstruksi Menggunakan Metode Life Cycle Cost pada Gedung Cordova Edupartment Semarang - Rini Pebri Utari; Sulianto; Abdul Samad; Agung Tri Wahono (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2023)
The Life Cycle Cost (LCC) method is a technique used to estimate future costs over the planned lifespan of a building, including construction and planning costs, operational costs, maintenance costs, and repair costs. This study aims to calculate the Life Cycle Cost of Cordova Edupartment Semarang and evaluate the building's feasibility against rental prices. The analysis results show that the Life Cycle Cost of the Cordova Edupartment Building over 50 years is IDR 1,676,611,471,421, consisting of direct costs of IDR 222,881,901,903 (13%), operational costs of IDR 477,956,421,626 (29%), maintenance costs of IDR 608,093,359,498 (36%), replacement costs of IDR 278,527,072,632 (17%), and bank loan interest of IDR 89,152,760,761 (5%). With a rental price of IDR 130,000/m² and an initial occupancy rate of 70%, the Net Present Value (NPV) is greater than 0, amounting to IDR 220,819,600,100. Thus, the Break Even Point is at 25.64 years, and the Internal Rate of Return (IRR) is a positive 9.35%, which is greater than the Minimum Acceptable Rate of Return (MARR) of 6.78%, indicating that the investment is feasible and profitable.